PENGGUNAAN LANTUNAN EHABLA SEBAGAI MEDIA PENDIDIKAN KARAKTER BAGI GENERASI MUDA - Wigati Yektiningtyas; Budi Rahayu (FKIP Universitas Cenderawasih, 2022)
Ehabla is one of the Sentani people’s oral poems. As a socio-cultural product, this song is the cultural asset that should be maintained because it expresses social and moral values that can be used as a medium of learning as well as a reflection of the socio-cultural dynamics of the Sentani community. One of the lessons contained in the ehabla is the value of character education. In fact, this ehabla is no longer recognized by some Sentani people, especially the younger generation. This is related to the loosening of social and traditional values that take place in villages near cities which are very likely to spread to other communities living on remote islands. Therefore, this paper wants to bring back this ehabla to life. This paper aims at exploring the educational values depicted in ehabla. The data of ehabla were collected in East Sentani, namely Asei Island, Waena, and Yokiwa through interviews and Focus Group Discussions with informants, i.e. tribal chiefs and Sentani elders in January-March 2022. From the data analysis, the educational values revealed from ehabla are (1) hard work, (2) cooperation, (3) harmony, (4) respect for others, (5) natural conservation, and (6) pride in their place of originKeywords: ehabla, oral poem, Sentani people, education values